Improved intraocular foreign body localization using orbital computed tomography data - N.A. Ulianova; Iu.V. Stasiuk; O.S. Sidak-Petretska; N.P. Tychina; Nataliia Bondar; Yu.M. Rodina (Ukrainian Society of Ophthalmologists, 2023)
Background: Detection and localization of an intraocular foreign body (IOFB) are essential for assessing the severity of injury and selecting an appropriate method for IOFB removal. Purpose: To improve the method of IOFB localization through the use of the Komberg-Baltin prosthesis while performing orbital computed tomography (CT) scans. Material and Methods: We reviewed the medical records of 6 patients with a penetrating corneal and/or scleral injury and an IOFB in the posterior segment. Patients had ultrasonography of the ocular anterior and posterior segments and Komberg-Baltin prosthesis-assisted CT of the orbit as per our method reported previously to verify the location of the IOFB. Orbital radiography was performed at the point of care. The results of radiography, ultrasonography and CT for each case were reviewed and compared. The final verification of IOFB location was performed preoperatively during a standard three-port 25-G pars plana vitrectomy with IOFB removal. Results: In 3 cases, intraoperative visualization during vitrectomy confirmed the results of preoperative IOFB imaging (radiography, ultrasonography and orbital CT). In these cases, an IOFB was a metallic fragment measuring 0.9 to 2.5 mm. In one case, a metallic IOFB was found by ultrasonography, but not by radiography. CT, when performed by our method, found an IOFB measuring 0.2 x 0.3 mm preretinally. In a patient with an IOFB (a wire measuring 10.0 x 1.0 mm, at 20 mm from the anatomical axis, and 9-11.5 mm from the limbal plane) and local retinal detachment, there was a discrepance between the foreign body location indentified by radiography and that identified by CT with the use of the Komberg-Baltin prosthesis. Large differences in the distance between the IOFB and the limbal plane and between the IOFB and the anatomical axis (4 mm and 5 mm, respectively) were caused by the mobility of the foreign body located beneath the retina. Conclusion: Localizing an IOFB using Komberg-Baltin prosthesis-assisted CT is advantageous to radiography due to an opportunity for accurate localization of a mobile IOFB with a patient in the position as similar as possible to his position during IOFB removal surgery (i.e., the supine position).